If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + 4 = 0 Reorder the terms: 2 + 4 + 3x = 0 Combine like terms: 2 + 4 = 6 6 + 3x = 0 Solving 6 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 0 + -6 3x = 0 + -6 Combine like terms: 0 + -6 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 4=f/ | | 5x(5x-7)=0 | | -1/(3-y) | | 2y=6y-220 | | Y^3-5y^2+6y-30= | | 9X+150-72X=150 | | -3+5(8+6r)=37 | | Z+8+-43+[-12]=20 | | 9/0.4 | | 4x+6-21x=19 | | 42x+15=32x | | y=6=5/2x-4 | | 28y^6-8y^3/4y^3 | | 3x+2-6=4 | | 2+8+-43+[-12]=20 | | |3x-3/9|1 | | 9xy-4x+y= | | 24x+5=42 | | 4y+8=4y+4 | | 3x-3/91 | | 3y-9=x+1 | | 8x^2-28x-23=0 | | 9xy-4xy+y= | | H+20= | | y^2-at+7by-7ab=0 | | -1=-1/5x | | 3x-2(x+6)=-24 | | 11q-145=13 | | 4(v-4)=6v-22 | | (-7)-0= | | 0.09xX=43.43 | | 3+7=-11+2x |